SURVEI POLA PEMBINAAN CABANG OLAHRAGA SEPAKBOLA USIA 12-17 TAHUN DI KABUPATEN NGADA - Oscar Daga; Yanuarius Ricardus Natal; Bernabas Wani (Jurnal Edukasi Citra Olahraga, 2022)
This study aims to determine the pattern of fostering the 12-17 year old football branch in Ngada Regency. This study uses a descriptive qualitative research design. The subjects in this study were the Head of the Ngada Regency Youth and Sports Education Office, the Chairperson of the Ngada Regency Askab, one of the coaches who had handled SSB in Ngada Regency, and soccer players. Collection methods used include interview methods, documentation methods, and observation methods. The data collection instruments in this study were interview guidelines, documentation guidelines in the form of photographs and observation guidelines. The data analysis method uses the interactive Miles and Huberman model with several techniques including: data reduction, data presentation, and drawing conclusions. The results of the study can be concluded, among others: (1) the youth football coaching system in Ngada district has been going well, (2) the management of youth football coaching in Ngada district is running quite well where the planning that is made goes according to what has been planned. plan, (3) The coach recruitment system in Ngada Regency still looks at experience as a former PS Ngada player and also has a coaching license, and (4 the football competition system in Ngada Regency is already running according to the agenda set by ASkab. However in recent years the competition in the district has decreased slightly, this is due to pandami covid-19